Factors Associated With Intention to Report Child Abuse among District Hospital Nurses in Iloilo, Philippines - Brian Christian S. Atencion; Aubrhey F. Alingalan; Ryan Michael F. Oducado; Justine Dynel N. Cordova; Ma. Carmela M. Dumaguing; Marian Therese T. Suaboksan (International Journal of Caring Sciences, 2019)
Background: Cases of child abuse are increasing. To report known and suspected child abuse is within the professional duty and legal responsibility of nurses. However, nurses' intention to report child abuse in the Philippines has not been widely investigated. Objective: This self-report, cross-sectional survey was designed to determine the factors relating to nurses' intention to report child abuse in the Philippine setting. Methods: 146 nurses assigned in the pediatric and emergency room of district hospitals in Iloilo participated in this study and data were collected using Feng & Levine's (2005) Child Abuse Report Intention Scale (CARIS). Spearman's rho was utilized to determine if there were significant associations between factors identified and nurses' intention to report child abuse. Results: More than half of staff nurses reported that they did not have pre-service education and in-service training regarding child abuse. There was underreporting of suspected child abuse among staff nurses and feeling uncertain of the evidence was the main reason stated. While nurses had low level of knowledge about child abuse and the reporting law, nurses had a positive attitude against child abuse. Nurses' intention to report child abuse was highly influenced by the opinions of people significant to them. They also had high perceived behavioral control in reporting child abuse. Attitude, subjective norm, and perceived behavioral control were significantly related to nurses' intention to report child abuse. Conclusion: This study highlights that more attention is required for the nurses' professional preparation, education, and training in managing child abuse. In addition, the results of this study support the Theory of Planned Behavior in determining factors associated with the intention to report child abuse among nurses in the Philippine setting.
Keywords: 330; child abuse; child neglect; theory of planned behavior; intention to report abuse; nurses; nursing